KORELASI, KERAGAMAN GENETIK, DAN HERITABILITAS KARAKTER AGRONOMI KACANG PANJANG POPULASI F3 KETURUNAN PERSILANGAN TESTA HITAM X LURIK - Nyimas Sa’diyah; Tjipto Roso Basoeki; Aprilia Eka Putri; Devi Maretha; Setyo Dwi Utomo (Universitas Lampung, 2009)
The objective of this study was to estimate correlation, variances, and heritability of agronomic characters of yardlong-bean F3 population derived from crosses between black and striped-black testa. An F3 population consisted 90 plants along with the two parents (20 plants per parent) were planted in unreplicated trial in Hajimena, Rajabasa, Bandar Lampung in 2008. Variables observed included flowering date, fresh-harvesting date, harvesting date, the number of flower stalks per plants,the number of pod per plant, the average number of locules per pod, the total number of seeds per plant, and the weight of 100 seeds. The results indicated that the estimate of genotypic and phenotypic variances and broad-sense heritability were high for all variables observed. The estimates were significant for the correlation between dry-seed weight per plant and the following variables: number of flower stalks per plant, number of pods per plant, the average number of loculs per pod, and the number of seeds per plants. Based on consumer demand and solid fresh peas can be obtained on the genotypes of the number 6, 7, 9, 11, 14, 19, 22, 28, 66, and 67. There are no pods which exceeds 50 cm in length.Keywords: correlation, heritability, variances, Vigna sinensis, yard-long beans